Sustainable transport conference (Thomas Telford, 2006)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a conference held on 7-8 September 2006.
Keywords: Transportation -- Environmental aspects -- Great Britain -- Congresses.; Transportation and state -- Great Britain -- Congresses.; Sustainable development -- Great Britain -- Congresses.; elektronické knihy; electronic books